2011
DOI: 10.1007/s10812-011-9448-3
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole derivatives as absorption probes for pluronics core-shell aggregates micropolarity investigation

Abstract: Their specific absorption parameters, sensitive to changes in micropolarity, were calibrated using the reference curves carried out in homogeneous tetraethyleneglycol/water mixtures. The probes were able to detect changes in the micelle micropolarity induced by hydration. Thus, with the help of calibration solutions, the effective local hydration of the polymeric chain sensed by the molecular probe solubilized in the guest aggregate was quantified and hypothetical relative locations of the probes in micelles h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Fluorescence spectroscopy studies have shown that the CMC of F127 depends on the temperature. For example, at 30 and 35°C, CMC equals 2.23 × 10 −5 and 1.03 × 10 −5 mol kg −1 , respectively [34]. Overall, the temperature, above which F127 micelles are formed, displays an inverse dependence on the F127 (logarithmic) composition, as demonstrated by Lin and Alexandridis [35].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Fluorescence spectroscopy studies have shown that the CMC of F127 depends on the temperature. For example, at 30 and 35°C, CMC equals 2.23 × 10 −5 and 1.03 × 10 −5 mol kg −1 , respectively [34]. Overall, the temperature, above which F127 micelles are formed, displays an inverse dependence on the F127 (logarithmic) composition, as demonstrated by Lin and Alexandridis [35].…”
Section: Resultsmentioning
confidence: 81%
“…Accordingly, if the increase of an F127 concentration is beyond ca 250 μmol L −1 , there is a pronounced increase in fluorescence until a plateau was attained past ca 500 μmol L −1 , which can be ascribed to the critical micellar concentration (CMC) for the F127, at the experiment temperature 25°C. There are, however, conflicting CMC values for F127 reported in the literature obtained through different methods, solvent and temperature conditions, as well as different manufacturers and batch [34]. This may be probably due to the degree of purity of the product supplied by different manufacturers.…”
Section: Resultsmentioning
confidence: 99%